2004
DOI: 10.1136/adc.2002.025478
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of cardiac troponin T in neonates with and without respiratory distress

Abstract: Aims: To establish a practical postnatal reference range for cardiac troponin T in neonates and to investigate concentrations in neonates with respiratory distress. Methods: Prospective investigation in a tertiary neonatal unit, recruiting infants with and without respiratory distress (sick and healthy infants respectively). Concentrations of cardiac troponin T were compared between sick and healthy infants, accounting for confounding variables. Results: A total of 162 neonates (113 healthy and 49 sick infants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
66
6
7

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(93 citation statements)
references
References 21 publications
14
66
6
7
Order By: Relevance
“…cTnT and NTpBNP were unaffected by gestation, birth weight, sex, chorioamnionitis and mode of delivery. This is consistent with the results of other groups [17][18][19][20] and suggests that assays of cTnT and Abbreviations: cTnT, cardiac troponin T; FS, shortening fraction; LA:Ao ratio, left atrial to aortic root ratio; Min-Max, minimum to maximum value; mVcfs, mean circumferential fiber shortening velocity; NTpBNP, N-terminal-pro-B type natriuretic peptide; PDA, patent ductus arteriosus. …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…cTnT and NTpBNP were unaffected by gestation, birth weight, sex, chorioamnionitis and mode of delivery. This is consistent with the results of other groups [17][18][19][20] and suggests that assays of cTnT and Abbreviations: cTnT, cardiac troponin T; FS, shortening fraction; LA:Ao ratio, left atrial to aortic root ratio; Min-Max, minimum to maximum value; mVcfs, mean circumferential fiber shortening velocity; NTpBNP, N-terminal-pro-B type natriuretic peptide; PDA, patent ductus arteriosus. …”
Section: Discussionsupporting
confidence: 90%
“…1 Infants requiring inotropes had higher cTnT compared to those who were normotensive but this did not reach statistical significance possibly due to the relatively small number of subjects. Clark SJ et al 18,22 showed a similar effect of inotropes on cTnT levels. Whether the rise in cTnT in hypotensive infants is a direct result of the inotropes or cardiovascular compromise occurring before delivery is unclear.…”
Section: Biochemical Markers and Preterm Infants A El-khuffash Et Almentioning
confidence: 82%
“…Since troponins do not occur in extracellular space, their appearance in serum is sensitive and specific marker of myocardium damage [2].They start to increase two hours after myocardial infarction or damage, and concentrations can remain raised for up to two weeks after a full thickness infarct [1]. Troponin rising has been described also in other clinical conditions with possible myocardial damage, such as, myocarditis [3], trauma [4], etc: every cardiac troponin value above the 99th percentile of the reference population in the typical clinical setting may be interpreted as myocardial damage with an increase in the risk of major cardiac events [5].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac troponin is a highly specific and very sensitive marker of myocardial necrosis recently used in newborns to rule out a myocardial ischaemia [1]. We report a case of an apparently healthy (except for jaundice) term newborn in which high values of troponin were not related to a documentable myocardial injury.…”
Section: Introductionmentioning
confidence: 92%
“…Clark et al found that the cTnT levels were significantly higher in sick infants than in healthy ones. The use of inotropic support and oxygen requirement were independently associated with higher cTnT levels (79).…”
Section: Patent Ductus Arteriosusmentioning
confidence: 99%